Using virtual world simulators (Second Life) in social work course assignments. (2016) - Anstadt, Scott P.; Bruster, Belinda; Girimurugan, Senthil B.
This article describes an initial exploration of Second Life (SL), a virtual platform that affords immersive opportunities for students to sensitise and educate themselves in a structured yet self-directed course-design framework. With the use of SL as a virtual reality platform, students are able to choose which resources are used to train them in basic navigation and which communities, representing a wide variety of cultural practices of interest to them, they would choose to study. In a two-year study, student attitudes of engagement and desire to learn cultural competencies through this media are compared, using two methods of course design introducing students to SL. Student surveys show significant improvement in SL navigation when entry into SL include interviews with key informants and a central teleportation hub for exploration to key sites. Student surveys show significant increase in student involvement and appreciation for the use of SL regarding the EPAS core competencies as published by the Council on Social Work Education in 2008 for cultural diversity and application to client assessment.